PERAN PENDIDIKAN KARAKTER DALAM PEMBENTUKAN SIKAP SOSIAL ANAK DI ERA DIGITAL - Novita Rahmawati; Syifa Nuraulia Ritonga (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
Character education plays a crucial role in shaping children's social attitudes in the digital era, characterized by the rapid development of technology and information. Children are frequently exposed to negative content such as hoaxes, cyberbullying, and information that does not support good moral values. This study aims to analyze the role of character education in helping children distinguish between the positive and negative influences of technology and integrate moral values ​​such as honesty, responsibility, and empathy in developing healthy social attitudes. Furthermore, this study also discusses the importance of digital literacy in supporting character education in cyberspace. The method used in this study is a literature study, collecting and analyzing various sources related to character education, digital literacy, and the impact of technology on children's social development. The results show that integrating technology into character education can be an effective tool for conveying moral values ​​through digital media, but must be done wisely and accompanied by teachers and parents. A balanced approach between technology and traditional methods, as well as collaboration between families, schools, and communities, is key to shaping children's character in the digital era.